2(2x+2)-3(x-4)=

Simple and best practice solution for 2(2x+2)-3(x-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x+2)-3(x-4)= equation:


Simplifying
2(2x + 2) + -3(x + -4) = 0

Reorder the terms:
2(2 + 2x) + -3(x + -4) = 0
(2 * 2 + 2x * 2) + -3(x + -4) = 0
(4 + 4x) + -3(x + -4) = 0

Reorder the terms:
4 + 4x + -3(-4 + x) = 0
4 + 4x + (-4 * -3 + x * -3) = 0
4 + 4x + (12 + -3x) = 0

Reorder the terms:
4 + 12 + 4x + -3x = 0

Combine like terms: 4 + 12 = 16
16 + 4x + -3x = 0

Combine like terms: 4x + -3x = 1x
16 + 1x = 0

Solving
16 + 1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + 1x = 0 + -16

Combine like terms: 16 + -16 = 0
0 + 1x = 0 + -16
1x = 0 + -16

Combine like terms: 0 + -16 = -16
1x = -16

Divide each side by '1'.
x = -16

Simplifying
x = -16

See similar equations:

| A/2=36 | | 84=78+n | | -x+7x=-12 | | -x^2+5=(4x-1)(4x-1) | | 4a+7a=7a+16 | | v/-4=13 | | -0.25+0.6= | | -0.25-0.6= | | (13m-11)=2m+5 | | -6(b-6)+4=88 | | 4.5s-s= | | 0.25-0.6= | | x*3+75=x*9-9 | | 18x11/(18x11)= | | 13m-11=2m+5 | | 2v-1=11 | | 63=2(6x-1)+5 | | 16a-5a= | | d+d+3d= | | -66=6(1+4m) | | 8(4n+2)=240 | | -3(2x-4)+(5x-3)= | | 11h+h= | | 3M-2p=0 | | 6-p^2=47 | | -(4x+6)-3(3x+6)= | | -8+4x=12+9x | | 5(2n-6)=-110 | | LA=3.14(r)(s) | | 4•/•2 | | 8=k+k | | P(X)=22.45 |

Equations solver categories